Waste to health: A review of waste derived materials for tissue engineering - Zamri M.F.M.A.; Bahru R.; Amin R.; Aslam Khan M.U.; Razak S.I.A.; Hassan S.A.; Kadir M.R.A.; Nayan N.H.M. (Elsevier Ltd, 2023)
Biocompatibility; Biodegradability; Biodegradable polymers; Sustainable development; Tissue; Waste disposal; Cost of manufacturing; Derived materials; Environmental sustainability; Polymer materials; Recent researches; Reducing waste; Tissue engineering applications; Tissue engineering